SISTEM INFORMASI MANAJEMEN KEARSIPAN DI SMK NEGERI 5 PADANG PROVINSI SUMATERA BARAT - Rifeldo Praguna; Efrizon Efrizon; Khairi Budayawan (Universitas Negeri Padang, 2017)
Mail archiving process in SMK 5 Negeri Padang still recorded manually. Therefore, we need an information system management of archives at SMK Negeri 5 Padang to assist in performing document archiving and can handle the process of legalization requests quickly archive. This information system aims to improve the efficiency, accuracy and security of archived documents. Hopefully, by the information system management of archives can alter the performance in SMK Negeri 5 Padang, especially in the archives in order to facilitate the archiving mail. In addition, by using the information in records management system will obtain the benefits of speed and convenience. The purpose of the speed here is through the use of this information system, the process of search, discovery, distribution and archive legalization done in quickly. Information system management of archives at SMK Negeri 5 Padang is designed to involve a web-based programming language HTML, CSS, JavaScript, and an object-oriented PHP, CodeIgniter, and MySQL as database. The system also uses an alias on addressing by applied to the address .htaccess file is actually as one of the security system. Users registered in this system have a private account to be entered into the system ID number and password with MD5 encryption. The results obtained from implementation information system management of archives in SMK 5 Negeri Padang is easier to manage the recording and archiving of mail that were once manual is now digital, and is helpful to demand legalized archives.Keywords : Information System, Archives, School, Web, CodeIgniter.